Sign in
Please select an account to continue using cracku.in
↓ →
If p, q are any two statements, the negation of the statement $$((\sim p \vee q) \wedge (p \vee \sim q)) \vee (p \wedge q)$$ is
$$(p \vee q) \wedge ((\sim p) \vee (\sim q))$$
$$(p \wedge q) \vee ((\sim p) \wedge (\sim q))$$
$$(p \wedge q) \wedge ((\sim p) \vee (\sim q))$$
$$(p \vee q) \wedge ((\sim p) \wedge (\sim q))$$
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Detailed syllabus & Topic-wise Weightage
By proceeding you agree to create your account
Free CAT Syllabus PDF will be sent to your email address soon !!!